2009
DOI: 10.1091/mbc.e08-08-0833
|View full text |Cite
|
Sign up to set email alerts
|

Caenorhabditis elegans FOS-1 and JUN-1 Regulateplc-1Expression in the Spermatheca to Control Ovulation

Abstract: Fos and Jun are components of activator protein-1 (AP-1) and play crucial roles in the regulation of many cellular, developmental, and physiological processes. Caenorhabditis elegans fos-1 has been shown to act in uterine and vulval development. Here, we provide evidence that C. elegans fos-1 and jun-1 control ovulation, a tightly regulated rhythmic program in animals. Knockdown of fos-1 or jun-1 blocks dilation of the distal spermathecal valve, a critical step for the entry of mature oocytes into the spermath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 52 publications
1
24
0
Order By: Relevance
“…To determine if depletion of filamin in the germline can account for the observed brood size defect we used the rrf-1(pk1417) mutant strain, which is defective for somatic RNAi, but has an apparently normal germline RNAi response (Sijen et al, 2001). The rrf-1(pk1417) animals have been used previously to demonstrate a somatic role for fos-1 in the spermatheca (Hiatt et al, 2009). We found that rrf-1(pk1417) mutants treated with fln-1 RNAi did not show a significantly different brood size (270.3 ± 45.1, n=8) from control RNAi treated rrf-1(pk1417) animals (307.2 ± 28.1, n=6; Student’s t-test, p=0.1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To determine if depletion of filamin in the germline can account for the observed brood size defect we used the rrf-1(pk1417) mutant strain, which is defective for somatic RNAi, but has an apparently normal germline RNAi response (Sijen et al, 2001). The rrf-1(pk1417) animals have been used previously to demonstrate a somatic role for fos-1 in the spermatheca (Hiatt et al, 2009). We found that rrf-1(pk1417) mutants treated with fln-1 RNAi did not show a significantly different brood size (270.3 ± 45.1, n=8) from control RNAi treated rrf-1(pk1417) animals (307.2 ± 28.1, n=6; Student’s t-test, p=0.1).…”
Section: Resultsmentioning
confidence: 99%
“…The plc-1(rx1) putative null animals phenocopy the exit defect of fln-1(tm545) animals, and retain multiple embryos in the spermatheca. PLC-1 is broadly expressed, and has been shown to have a role in embryogenesis, in addition to its role during ovulation (Hiatt et al, 2009; Vazquez-Manrique et al, 2008). We hypothesized that, if stretching induced by accumulated embryos causes the actin to be redistributed to the cell boundaries, the actin cytoskeleton in plc-1(rx1) spermathecal cells might be similarly disrupted.…”
Section: Resultsmentioning
confidence: 99%
“…The table below lists some well-known IEGs expressed in the nervous system. Most IEGs found in mammals are conserved across many species, from invertebrates such as C. elegans [53], Aplysia [54] and Drosophila [55] to vertebrates, but only a subset have been tested to see whether they are rapidly induced by neuronal activity.…”
Section: Figurementioning
confidence: 99%
“…Indeed, mutations in plc-1 or plc-1(RNAi) cause spermathecal entry and exit defects (Kariya et al 2004; Yin et al 2004). PLC-1 expression in the spermatheca requires the FOS-1/JUN-1 heterodimeric transcriptional activator (Hiatt et al 2009). RNAi of fos-1 or jun-1 disrupts ovulation and this defect is rescued by expression of PLC-1 in the spermatheca (Hiatt et al 2009).…”
Section: 2 Meiotic Maturation In C Elegansmentioning
confidence: 99%